The Dynamics of Rights and Obligations in Long-Distance Marriages: An Islamic Law Perspective on a Case Study in Palangka Raya City - Rizky, Ghina Aulia; Syaikhu, Syaikhu; Ahmad, Sabarudin (CV. Social Politic Genius (SIGn), 2025)
Long-distance marriage presents serious challenges to the fulfillment of spousal rights and obligations, potentially triggering conflict and household disintegration. This study aims to conduct an in-depth analysis of these dynamics through a qualitative-empirical case study of a couple in Palangka Raya City. Data were collected through in-depth interviews, observation, and documentation, and subsequently analyzed interpretively using the frameworks of the Compilation of Islamic Law and Maqāṣid al-Syarī’ah. The key finding of this research reveals that the husband’s sustained failure to fulfill his obligation of financial support triggered an extreme role reversal, wherein the wife became the sole financial provider. This imbalance became the root of communication erosion, the creation of emotional distance, and the accumulation of conflicts culminating in divorce. It is concluded that the marital disintegration was not caused solely by physical distance; the primary factor was the couple’s inability to renegotiate their roles and responsibilities equitably. This situation, both juridically and philosophically, contradicts the principles of justice and benefit in Islamic family law. This research contributes fundamental empirical data to the contemporary discourse on fiqh concerning modern marriage.